Feline heartworm (Dirofilaria immitis) infection: first case report of serological diagnosis in Brazil, confirmed by molecular assay - BARBARA B. PEREIRA; BETHÂNIA F. BASTOS; LUCAS KEIDEL; DANIELA LELES; BEATRIZ BRENER (Anais da Academia Brasileira de Ciências, 2018)
Abstract The clinical importance of heartworm infection in cats has indeed increased in recent years. Dirofilaria immitis infection has been reported worldwide in cats and continues to be regularly diagnosed in endemic areas. The diagnosis can be overlooked easily, especially in Brazil, where there is not a specific feline immunodiagnostic test, forcing the veterinarians to use a test made for the canine host. In 2015, a 10-year-old female neutered cat was diagnosed with D. immitis using an antigen serological test, based on imunocromatography and designed for dogs. The modified Knott test was negative. As the disease progressed, the cat showed clinical signals of respiratory distress, such as dyspnoea and polypnea in addition to prostration and emaciation, and died a few weeks after the diagnosis. During necropsy, one adult nematode was found in the pulmonary artery. D. immitis infection was confirmed by molecular amplification, performed in the worm fragment. This is the first report of serological diagnosis of feline dirofilariasis in Brazil. A chemoprophylaxis routine in cats should be done, as is done in dogs from endemic areas.